Castanea crenata honey reduces influenza infection by activating the innate immune response - Kwon, Eun-Bin; Kim, Se-Gun; Kim, Young Soo; Kim, Buyun; Han, Sang Mi; Lee, Hye Jin; Choi, Hong Min; Choi, Jang-Gi (Frontiers in Immunology, 2023)
Influenza is an acute respiratory disorder caused by the influenza virus and is associated with prolonged hospitalization and high mortality rates in older individuals and chronically ill patients. Vaccination is the most effective preventive strategy for ameliorating seasonal influenza. However, the vaccine is not fully effective in cases of antigenic mismatch with the viral strains circulating in the community. The emergence of resistance to antiviral drugs aggravates the situation. Therefore, developing new vaccines and antiviral drugs is essential. Castanea crenata honey (CH) is an extensively cultivated food worldwide and has been used as a nutritional supplement or herbal medicine. However, the potential anti-influenza properties of CH remain unexplored. In this study, the in vitro and in vivo antiviral effects of CH were assessed. CH significantly prevented influenza virus infection in mouse Raw264.7 macrophages. CH pretreatment inhibited the expression of the viral proteins M2, PA, and PB1 and enhanced the secretion of proinflammatory cytokines and type-I interferon (IFN)-related proteins in vitro. CH increased the expression of RIG-1, mitochondrial antiviral signaling (MAVS) protein, and IFN-inducible transmembrane protein, which interferes with virus replication. CH reduced body weight loss by 20.9%, increased survival by 60%, and decreased viral replication and inflammatory response in the lungs of influenza A virus-infected mice. Therefore, CH stimulates an antiviral response in murine macrophages and mice by preventing viral infection through the RIG-1-mediated MAVS pathway. Further investigation is warranted to understand the molecular mechanisms involved in the protective effects of CH on influenza virus infection.